Sistem Informasi Distribusi Bank Sampah Berbasis Website With Oil Counter Pada Bank Sampah Melati Bersih Tangerang Selatan - Masriza, Fahmi Fiqih; Wijayanto, Dani; Djayusman, Ismoyo Nugroho; Priyatna, Ade (TIN: Terapan Informatika Nusantara, 2021)
Waste bank in principle operates like a bank in general, in the process customers come saving garbage and at a predetermined time can withdraw money from the waste that has been saved by the customer. Waste is waste material produced from household waste, offices and others. Then it needs to be handled in addressing problems caused by garbage, one of which is with the existence of waste banks. Processed waste in the form of organic waste such as, plastic waste, paper, metal and others. The waste is processed into various handicrafts or sold to other parties to be used as raw materials. In the processing of data in the waste bank is still done by manual that is written on the general ledger or agenda book. The officer must record every time a transaction occurs. Therefore we are interested to create a waste bank distribution information system with oil counter that can help officers in the transaction process and customers check the balance independently